Ectoparasite Infestation among Stray Cats around Surabaya Traditional Market, Indonesia - Shifa Fauziyah; Abdul Hadi Furqoni; Norma Farizah Fahmi; Adi Pranoto; Pradika Gita Baskara; Lensa Rosdiana Safitri; Zukhaila Salma (Universitas Gadjah Mada, 2020)
This study was conducted to determine the prevalence of ectoparasite infestation among stray cats around Surabaya traditional markets. A total of 305 stray cats were collected around 17 traditional markets in Surabaya City and were examined for the presence of fleas with a fine-toothed flea comb. Surveys were conducted during May-June 2019. 228 of 305 stray cats (74.75%) were infested with one species of ectoparasite. The average number of C. felis in every cat was 2.54, while the number of F. subrostratus in every cat was 0.33. Additional data about the gender, pregnancy/maternity, and bodyweight of every cat were recorded. The result of chi-square test shows that there is a significant difference between gender, pregnancy status, and bodyweight by the occurrence of ectoparasites (p=0.008; p=0.00; p=0.00). A total of 878 ectoparasites consisting of flea and lices, namely Ctenocephalides felis (88.27%) as the dominant ectoparasite, followed by Felicola subrostratus (11.73%). The highest infection rate (prevalence) of ectoparasite was found in Pucang Market (16.81%), while the lowest prevalence was found in Mulyorejo Market (0.8%). Coinfection was observed in only a few cats (1.63%). Multiple Regression showed that pregnancy is the most influential factor in the occurrence of fleas (p=0.000). These results should be taken into account among health workers to prevent a possible outbreak of zoonotic diseases caused by fleas.